Preparation method of bimetallic functionalized organic framework material and application of bimetallic functionalized organic framework material in carbon dioxide adsorption separation

By replacing H+ to Ag+ in UiO-66 material, bimetallic functional UiO-66-SO3Ag material was prepared, which solved the problem of low CO2 adsorption and separation efficiency in the prior art, and achieved efficient and low-cost CO2 selectivity Adsorption and separation effects.

CN119119492APending Publication Date: 2024-12-13XUZHOU UNIV OF TECH
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202410097916.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-01-24
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

Among the existing CO2 capture and separation technologies, there is a lack of new materials for efficient adsorption and separation of CO2, especially in terms of cost and production efficiency.

Method used

By ion exchange method, H+ in the sulfonic acid-functionalized UiO-66 material was replaced with Ag+, and a bimetallic functionalized UiO-66-SO3Ag material was prepared. The π-complexing effect of Ag+ and double bonds was used to improve the material's CO2 selective adsorption capacity.

Benefits of technology

It significantly improves the selective adsorption and separation capacity of CO2, reduces production costs and improves yields, and has good application prospects in the treatment of carbon dioxide excess in the environment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119119492A_ABST
    Figure CN119119492A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a bimetal functionalized organic framework material and application of the bimetal functionalized organic framework material in carbon dioxide adsorption and separation, the preparation method of the bimetal functionalized organic framework material comprises the following steps: by utilizing the characteristic that Ag < + > can form a relatively strong pi complexing action with double bonds, by adopting an ion exchange method, taking sulfonic acid functionalized UiO-66 as a carrier, and by adopting an ion exchange method, preparing the bimetal functionalized organic framework material. H < + > is replaced with Ag < + >, and bimetal functionalized UiO-66-SO3Ag is prepared; the product yield is effectively improved; according to the preparation method of the bimetallic functionalized organic framework material UiO-66-SO3Ag, the raw materials are cheap and easy to obtain, the synthesis conditions are simple, the yield is high, and the cost is low; due to the unique pore structure and the bimetal active site effect, the carbon dioxide adsorbent has high selective adsorption and separation capacity on carbon dioxide, and has good application prospects in the aspect of treating carbon dioxide excess in the environment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of metal organic framework material preparation and application, and in particular to a method for preparing a bimetallic functionalized organic framework material and its application in carbon dioxide adsorption and separation. Background Art

[0002] CO2 emission reduction can be achieved by developing renewable energy, improving energy utilization efficiency and developing CO2 capture and separation technology. Since the development and utilization of renewable energy in traditional coal-fired power plants has not formed a scale and there is little room for improving energy utilization efficiency, CO2 capture and separation technology has become the main method to reduce CO2 emissions. CO2 capture and separation technology is one of the key technologies for carbon emission reduction in my country. It refers to the separation and purification of industrially produced CO2 through carbon capture technology, and then putting it into new production, so that CO2 can be recycled, or it can be sealed through carbon storage methods. There are many carbon capture and separation methods in CO2 capture and separation technology. According to the capture mechanism, it can be divided into membrane separation method, adsorption method, solvent absorption method and other categories. The adsorption method is considered to be the most promising CO2 capture and separation technology due to its low energy consumption, low corrosion and simple operation. The core of this technology is to develop new materials for efficient adsorption and separation of CO2.

[0003] Metal-Organic Frameworks (MOFs) are a type of porous material that has emerged in recent years. They are considered to be the most promising gas storage and separation materials due to their large specific surface area, ultra-high porosity, and controllable pore structure and size. Summary of the invention

[0004] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a method for preparing a bimetallic functionalized organic framework material and its application in carbon dioxide adsorption and separation. The method for preparing the bimetallic functionalized organic framework material is as follows: using Ag + The sulfonic acid functionalized UiO-66 was used as the carrier to form a strong π complex with double bonds by ion exchange method. + Replaced with Ag + , bimetallic functionalized UiO-66-SO3Ag is prepared; the product yield is effectively improved; the preparation method of the bimetallic functionalized organic framework material UiO-66-SO3Ag of the present invention has cheap and easily available raw materials, simple synthesis conditions, high yield and low cost; due to the unique pore structure and the effect of bimetallic active sites, it has a strong selective adsorption and separation ability for carbon dioxide, and has good application prospects in controlling excess carbon dioxide in the environment.

[0005] In order to achieve the above technical effects, the following technical solutions are adopted:

[0006] A method for preparing a bimetallic functionalized organic framework material comprises the following steps:

[0007] Step S1: UiO-66 synthesis

[0008] 2-Sodium sulfoterephthalate, zirconium chloride, and terephthalic acid are dissolved in glacial acetic acid and DMF, and after ultrasonic treatment, they are transferred to a reactor, heated for reaction, and then cooled; the generated solid product is filtered and washed with DMF and methanol respectively; the solid product is dried to obtain a brown powder, namely UiO-66;

[0009] Step S2: Synthesis of UiO-66-SO3Ag

[0010] Dissolve AgNO3 in acetonitrile, then add UiO-66-SO3H; stir the reaction under light protection, filter and collect the solid, and rinse with water; dry the washed solid material and store it in vacuum to obtain UiO-66-SO3Ag.

[0011] Furthermore, in step S1, the molar ratio of monosodium 2-sulfoterephthalate to terephthalic acid is 1:2-1:4; and the molar number of zirconium chloride is the sum of the molar numbers of monosodium 2-sulfoterephthalate and terephthalic acid.

[0012] Furthermore, in step S1, the volume ratio of glacial acetic acid to DMF is 1:8-1:10.

[0013] Furthermore, the ultrasonic treatment time in step S1 is 10-20 min; and the reactor is a polytetrafluoroethylene-lined stainless steel autoclave.

[0014] Furthermore, in step S1, the reaction temperature is 110-150°C, the reaction time is 20-40h; the cooling temperature is 20-30°C; the generated solid product is filtered and washed 2-4 times with DMF and methanol respectively; and the drying condition is drying in a vacuum drying oven at 60-80°C for 6-12h.

[0015] Furthermore, in step S2, the mass ratio of silver nitrate to UiO-66-SO3H is 51-272:107-214; the acetonitrile is a mixed solution of acetonitrile and water, wherein the volume ratio of acetonitrile to water is 1:0.8-1:1.2.

[0016] Furthermore, in step S2, the reaction temperature is 28-30° C., and the light-proof reaction time is 8-15 hours.

[0017] Furthermore, in step S2, the mixture is rinsed with water for 3-5 times; and the drying condition is 80-120° C. for 12-24 hours.

[0018] A bimetallic functionalized organic framework material is prepared by adopting the preparation method.

[0019] Application of the above-mentioned bimetallic functionalized organic framework materials in carbon dioxide adsorption and separation.

[0020] For example: selective adsorption of carbon dioxide in a nitrogen and carbon dioxide mixer.

[0021] The beneficial effects of the present invention are:

[0022] 1. The present invention utilizes Ag + It has the characteristic of forming strong π complex with double bonds. Through ion exchange method, H + Replaced with Ag + , effectively improving the yield of UiO-66-SO3Ag;

[0023] 2. The bimetallic functionalized metal organic framework prepared by the present invention significantly improves the selective adsorption capacity of carbon dioxide due to its unique pore structure and bimetallic active sites. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. The drawings in the following description are merely embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the provided drawings without paying any creative work.

[0025] Figure 1 The XRD pattern of the bimetallic functionalized metal organic framework prepared in Example 2 of the present application and the comparison diagram of UiO-66-SO3H and UiO-66;

[0026] Figure 2 Scanning electron microscopy and mapping images of the bimetallic functionalized metal organic framework prepared in Example 2 of the present application;

[0027] Figure 3 EDX spectrum of the bimetallic functionalized metal organic framework prepared in Example 2 of the present application;

[0028] Figure 4 Infrared absorption spectrum of the bimetallic functionalized metal organic framework prepared in Example 2 of the present application;

[0029] Figure 5 Thermogravimetric analysis spectrum of the bimetallic functionalized metal organic framework prepared in Example 2 of the present application;

[0030] Figure 6Physical adsorption diagram of the bimetallic functionalized metal organic framework prepared in Example 2 of the present application;

[0031] Figure 7 Adsorption isotherms of CO2 and N2 at different temperatures and 1 bar for the bimetallic functionalized metal organic framework prepared in Example 2 of the present application;

[0032] Figure 8 Adsorption isotherms of CO2 and N2 at different temperatures and 1 bar for the bimetallic functionalized metal organic framework prepared in Comparative Example 1 of the present application;

[0033] Fig. 9 The competitive adsorption curve of the bimetallic functionalized metal organic framework prepared in Example 2 of the present application for a CO2 / N2 (15 / 85) mixed gas simulated by IAST theory;

[0034] Fig.10 Calculation results of IAST separation constants of the bimetallic functionalized metal organic framework prepared in Example 2 of the present application;

[0035] Fig.11 Schematic diagram of the isothermal adsorption energy of CO2 by the bimetallic functionalized metal organic framework prepared in Example 2 of the present application;

[0036] Fig.12 Adsorption isotherm of the bimetallic functionalized metal organic framework prepared in Example 2 of the present application for repeated adsorption of CO2 for 5 times;

[0037] Fig.13 Adsorption isotherm of CO2 for the bimetallic functionalized metal organic framework prepared in Example 2 of the present application after exposure to air (95%) for 2 days. DETAILED DESCRIPTION

[0038] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0039] It should be noted that the following detailed descriptions are exemplary and are intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs.

[0040] It should be noted that the terms used herein are only for describing specific embodiments and are not intended to limit exemplary embodiments according to the present invention. As used herein, unless the context clearly indicates otherwise, the singular form is also intended to include the plural form. In addition, it should be understood that when the terms "comprising" and / or "including" are used in this specification, it indicates the presence of features, steps, operations and / or combinations thereof.

[0041] A method for preparing a bimetallic functionalized organic framework material, comprising the following steps:

[0042] Embodiment 1:

[0043] (1) 0.05 mmol of monosodium 2-sulfoterephthalate, 0.2 mmol of zirconium chloride, 0.15 mmol of terephthalic acid and 1 mL of glacial acetic acid were dissolved in 9 mL of DMF, and after ultrasonic treatment for 10 min, transferred to a polytetrafluoroethylene-lined stainless steel autoclave, heated at 120°C for 20 h, and then naturally cooled to 20°C. The generated solid product was filtered and washed three times with DMF and methanol respectively. The solid was dried in a vacuum oven at 120°C for 24 h to obtain a brown powder.

[0044] (2) First, 51 mg of AgNO3 was dissolved in 16 mL of CH3CN / H2O (V:V=1:1) solution, and then 107 mg of UiO-66-SO3H was added. Stirring was carried out at 25°C in the dark for 12 hours, and the solid was collected by filtration and rinsed with water three times. The above steps were repeated twice, and the washed material was dried at 60°C for 12 hours, weighing 115 mg, with a yield of 91%, and stored in a vacuum desiccator for future use.

[0045] Embodiment 2:

[0046] (1) 0.06 mmol of monosodium 2-sulfoterephthalate, 0.24 mmol of zirconium chloride, 0.18 mmol of terephthalic acid and 1 mL of glacial acetic acid were dissolved in 9 mL of DMF, and after ultrasonic treatment for 15 min, transferred to a polytetrafluoroethylene-lined stainless steel autoclave, heated at 150°C for 30 h, and then naturally cooled to 25°C. The resulting solid product was filtered and washed three times with DMF and methanol respectively. The solid was dried in a vacuum oven at 70°C for 24 h to obtain a brown powder.

[0047] (2) First, 272 mg of AgNO3 was dissolved in 16 mL of CH3CN / H2O (V:V=1:1) solution, and then 214 mg of UiO-66-SO3H was added. Stirred for 15 hours at 25°C in the dark, filtered to collect the solid, and rinsed with water three times. Repeat the above steps twice, and the washed material was dried at 120°C for 12 hours, weighing 242 mg, with a yield of 94.1%. Store in a vacuum desiccator for future use.

[0048] Embodiment 3:

[0049] (1) 0.12 mmol of monosodium 2-sulfoterephthalate, 0.48 mmol of zirconium chloride, 0.36 mmol of terephthalic acid and 2 mL of glacial acetic acid were dissolved in 18 mL of DMF, and after ultrasonic treatment for 20 min, transferred to a polytetrafluoroethylene-lined stainless steel autoclave, heated at 140°C for 30 h, and then naturally cooled to 25°C. The resulting solid product was filtered and washed three times with DMF and methanol respectively. The solid was dried in a vacuum oven at 80°C for 24 h to obtain a brown powder.

[0050] (2) First, 68 mg of AgNO3 was dissolved in 16 mL of CH3CN / H2O (V:V=1:1) solution, and then 214 mg of UiO-66-SO3H was added. Stirred for 12 hours at 25°C in the dark, filtered to collect the solid, and rinsed with water three times. Repeat the above steps twice, and the washed material was dried at 120°C for 12 hours, weighing 220 mg, with a yield of 85.6%. Store in a vacuum desiccator for future use.

[0051] Comparative Example 1: Synthesis of UiO-66 as a control

[0052] 0.24 mmol of zirconium chloride and 0.24 mmol of terephthalic acid were weighed and dissolved in 25 mL of DMF and ultrasonicated for 15 min. The resulting solution was then transferred to a PTFE-lined stainless steel autoclave. The reaction flask was tightly covered with a PTFE-lined lid and heated in an oven at 120 °C for 24 h. After cooling to room temperature, a clear phase separation between the solid and the solvent was observed. The crude product was collected by centrifugation and then thoroughly washed three times with DMF and methanol. Subsequently, the purified sample was dried in a vacuum oven at 100 °C for 24 h.

[0053] The bimetallic functionalized organic framework material prepared in Example 2 and the UiO-66 of Comparative Example 1 were evaluated and characterized:

[0054] Figure 1 The XRD pattern of the bimetallic functionalized metal organic framework prepared in Example 2 and the comparison between UiO-66-SO3H and UiO-66. By comparison, it can be seen that the main characteristic peaks of UiO-66-SO3H and UiO-66 are exactly the same, indicating that UiO-66-SO3H and UiO-66 have the same skeleton structure. In addition, Ag + Comparison of the XRD patterns of UiO-66-SO3H and UiO-66-SO3Ag before and after exchange revealed that the skeleton structure of UiO-66-SO3H can still be well maintained.

[0055] Figure 2The scanning electron microscope and mapping images of the bimetallic functionalized metal organic framework prepared in Example 2. It can be seen from the figure that UiO-66-SO3Ag has a porous structure and a rough surface morphology, which is conducive to the adsorption of gas. From the mapping image, it can be seen that the main characteristic elements Ag, Zr, O, and S are evenly distributed.

[0056] Figure 3 This is the EDX spectrum of the bimetallic functionalized metal organic framework prepared in Example 2. From the spectrum and Table 1, it can be seen that the contents of Ag, Zr, O, and S are 1.94%, 10.57%, 85.46%, and 2.03%, respectively. Calculations show that about 94% of -SO3H is converted into -SO3Ag;

[0057] Table 1 Calculation and statistics of each element content

[0058]

[0059]

[0060] Figure 4 This is the infrared absorption spectrum of the bimetallic functionalized metal organic framework prepared in Example 2. As can be seen from the figure, UiO-66-SO3Ag and UiO-66-SO3H have an absorption spectrum of 1400-1750 cm -1 There are similar absorptions at 900~1115cm -1 The absorption peak of Ag-O bending vibration is shown in Figure 2, which indicates that Ag ions are successfully introduced into UiO-66-SO3H.

[0061] Figure 5 This is the thermogravimetric analysis spectrum of the bimetallic functionalized metal organic framework prepared in Example 2. From the comparison spectrum, it can be seen that UiO-66-SO3Ag has better thermal stability than UiO-66-SO3H. In the first stage, before 150°C, the mass continues to decrease, corresponding to the removal of water molecules physically adsorbed on the surface of the material, guest water molecules, and solvent molecules; in the second stage, UiO-66-SO3Ag can maintain a mass fraction of 85% before 430°C, indicating that the skeleton structure is thermally stable and remains intact; after 430°C, the mass changes significantly, corresponding to the decomposition of the material skeleton. This shows that Ag + The introduction of maintains the excellent thermal stability of UiO-66 material.

[0062] Figure 6The N2 adsorption isotherm of the bimetallic functionalized metal organic framework prepared in Example 2 at 77K; the N2 adsorption-desorption isotherms of UiO-66-SO3H and UiO-66-SO3Ag at 77K are typical type I adsorption isotherms. It can be seen that the introduction of Ag ions reduces the adsorption amount of N2. By calculation, the BET specific surface areas of UiO-66-SO3H and UiO-66-SO3Ag are 1210 and 1103 m 2 g -1 , the corresponding pore volume increases from 0.162cm 3 g -1 Reduced to 0.130cm 3 g -1 The inset is the pore size distribution curve obtained by the HK model from the N2 adsorption curve at 77K. It can be seen that the pore size is mainly distributed in Between, and Ag + The introduction of does not affect the pore size distribution basically, but reduces its cumulative pore volume, so the N2 adsorption amount decreases.

[0063] Figure 7 The adsorption isotherms of the bimetallic functionalized metal organic framework prepared in Example 2 for CO2 and N2 at different temperatures and 1 bar; Figure 8 The adsorption isotherms of CO2 and N2 at different temperatures and 1 bar for the bimetallic functionalized metal organic framework prepared in comparative example 1. It can be seen that the adsorption isotherms of UiO-66-SO3H and UiO-66-SO3Ag have similar trends. The adsorption capacity of CO2 and N2 increases with increasing pressure and decreasing temperature, which is consistent with the typical physical adsorption characteristics of microporous materials. At the same time, the variation of adsorption amount with pressure and temperature indicates that the material is suitable for separation processes such as pressure swing adsorption and temperature swing adsorption. At different temperatures, the N2 adsorption of UiO-66-SO3H and UiO-66-SO3Ag is similar and low. Although the specific surface area and pore volume of UiO-66-SO3Ag are lower than those of UiO-66-SO3H, the CO2 adsorption of UiO-66-SO3Ag is higher than that of UiO-66-SO3H at 293K, 303K, and 313K. With the increase of pressure, the absorption of CO2 increases sharply. There is no adsorption saturation in the pressure range of the study, indicating that a higher CO2 adsorption capacity can be obtained at a higher pressure. In addition, the CO2 adsorption of UiO-66-SO3Ag reaches 52.7 cm at 1 bar and 293K. 3 g -1 (2.35mmol g -1 ), the CO2 adsorption capacity of UiO-66-SO3H under the same conditions is 32.3 cm 3 g -1(1.44mmol g -1 ), the introduction of Ag ions increased the CO2 adsorption capacity by 61%. At 1 bar, 293 K, the N2 adsorption capacity of UiO-66-SO3Ag was only 6.0 cm 3 g -1 (0.27mmol g-1). It can be seen that UiO-66-SO3Ag can effectively achieve the selective adsorption of CO2-N2 within the room temperature range.

[0064] Fig. 9 The competitive adsorption curve of CO2 / N2 (15 / 85) mixed gas simulated by IAST theory for the bimetallic functionalized metal organic framework prepared in Example 2. For the CO2 / N2 (15 / 85) two-component mixed gas, UiO-66-SO3Ag can adsorb more CO2 than UiO-66-SO3H at the same temperature, and at 293K, the CO2 adsorption amount reaches 0.568mmol / g, while the N2 adsorption amount is only 0.241mmol / g.

[0065] Fig.10 The calculation results of the IAST separation constant of the bimetallic functionalized metal organic framework prepared in Example 2. At 1 kPa, the IAST separation constants of UiO-66-SO3Ag for the CO2 / N2 (15 / 85) mixed gas reached 8.71 (293K), 8.18 (303K), and 11.63 (313K), respectively. As the pressure increased to 110 kPa, the IAST adsorption selectivity increased to 13.42 (293K), 11.59 (303K), and 17.56 (313K), respectively.

[0066] Fig.11 Schematic diagram of the isothermal adsorption energy of CO2 for the bimetallic functionalized metal organic framework prepared in Example 2. As shown in the figure, in the initial state, the isothermal adsorption energy of CO2 for UiO-66-SO3H and UiO-66-SO3Ag is 23.4KJ / mol and 27.8KJ / mol respectively. With the increase of adsorption amount, the adsorption heat of CO2 for UiO-66-SO3H gradually decreases; while the adsorption heat of CO2 for UiO-66-SO3Ag gradually increases with the increase of adsorption amount. It can be clearly seen that Ag + The introduction of Ag significantly increased the initial adsorption heat of CO2 on the MOFs framework, and the CO2 adsorption performance gradually increased with the increase of adsorption amount. This is because CO2 molecules and open Ag + There is a strong electrostatic interaction between metal sites, which polarizes the CO2 molecules. This polarization further strengthens the force on the subsequently adsorbed CO2 molecules.

[0067] Fig.12This is the adsorption isotherm of CO2 repeatedly adsorbed 5 times by the bimetallic functionalized metal organic framework prepared in Example 2. Most MOFs materials with unsaturated metal sites are not very stable to moisture in the air. It can be seen from the figure that after 5 adsorption experiments of CO2 by UiO-66-SO3Ag, the adsorption amount of CO2 has basically not changed and still maintains the initial adsorption level.

[0068] Fig.13 The adsorption isotherm of CO2 for the bimetallic functionalized metal organic framework prepared in Example 2 after exposure to air (95%) for 2 days. UiO-66-SO3Ag was exposed to air (95% humidity) for 2 days and vacuum degassed at 150°C for 8 hours. The adsorption results of CO2 are shown in the figure. After 2 days of exposure to air, the adsorption amount of CO2 has almost no change, which proves that UiO-66-SO3Ag can maintain the stability of its structure and active sites well whether it is repeatedly used or exposed to air.

[0069] Comparative Example 2:

[0070] First, 300 mg of Cu(NO3)2 was dissolved in 16 mL of CH3CN / H2O (V:V=1:1) solution, and then 214 mg of UiO-66-SO3H was added. Stirred for 15 hours at 25°C in the dark, filtered to collect the solid, and rinsed with water three times. Repeat the above steps twice, and the washed material was dried at 120°C for 12 hours, weighing 228 mg, with a yield of 91.1%. Store in a vacuum desiccator for future use.

[0071] Using the above method, XRD characterization showed that (UiO-66-SO3)2Cu was not successfully prepared, and the corresponding (UiO-66-SO3)2M1 and (UiO-66-SO3)3M2 (M1=Ca) were not obtained by using different divalent and trivalent metals. 2+ Mg 2+ ,Co 2+ ; M2=Fe 3+ ,Al 3+ ). This may be mainly due to the large structure of the ligand, which makes it difficult to exchange ions with high-valent metals. At the same time, comparative experiments were conducted using potassium nitrate and sodium nitrate. The results showed that although UiO-66-SO3K or UiO-66-SO3Na can be formed, their thermal stability and selective adsorption capacity of carbon dioxide are much lower than those of UiO-66-SO3Ag.

[0072] In summary, the present invention discloses a method for preparing a bimetallic functionalized organic framework material and its application in carbon dioxide adsorption and separation. The method for preparing the bimetallic functionalized organic framework material is as follows: using Ag +The sulfonic acid functionalized UiO-66 was used as the carrier to form a strong π complex with double bonds by ion exchange method. + Replaced with Ag + , bimetallic functionalized UiO-66-SO3Ag is prepared; the product yield is effectively improved; the preparation method of the bimetallic functionalized organic framework material UiO-66-SO3Ag of the present invention has cheap and easily available raw materials, simple synthesis conditions, high yield and low cost; due to the unique pore structure and the effect of bimetallic active sites, it has a strong selective adsorption and separation ability for carbon dioxide, and has good application prospects in controlling excess carbon dioxide in the environment.

[0073] At this point, those skilled in the art recognize that, although the embodiments of the present invention have been shown and described in detail herein, many other variations or modifications that conform to the principles of the present invention can still be directly determined or derived based on the contents disclosed in the present invention without departing from the spirit and scope of the present invention. Therefore, the scope of the present invention should be understood and recognized as covering all such other variations or modifications.

Claims

1. A method for preparing a bimetallic functionalized organic framework material, characterized in that: The preparation method comprises the following steps: Step S1: UiO-66 synthesis 2-Sodium sulfoterephthalate, zirconium chloride, and terephthalic acid are dissolved in glacial acetic acid and DMF, and after ultrasonic treatment, they are transferred to a reactor, heated for reaction, and then cooled; the generated solid product is filtered and washed with DMF and methanol respectively; the solid product is dried to obtain a brown powder, namely UiO-66; Step S2: Synthesis of UiO-66-SO3Ag Dissolve AgNO3 in acetonitrile, then add UiO-66-SO3H; stir the reaction under light protection, filter and collect the solid, and rinse with water; dry the washed solid material and store it in vacuum to obtain UiO-66-SO3Ag.

2. A method for preparing a bimetallic functionalized organic framework material as claimed in claim 1, characterized in that: In step S1, the molar ratio of monosodium 2-sulfoterephthalate to terephthalic acid is 1:2-1:4; the molar number of zirconium chloride is the sum of the molar numbers of monosodium 2-sulfoterephthalate and terephthalic acid.

3. A method for preparing a bimetallic functionalized organic framework material as claimed in claim 1, characterized in that: In step S1, the volume ratio of glacial acetic acid to DMF is 1:8-1:

10.

4. A method for preparing a bimetallic functionalized organic framework material as claimed in claim 1, characterized in that: The ultrasonic treatment time in step S1 is 10-20 minutes; the reactor is a stainless steel autoclave lined with polytetrafluoroethylene.

5. A method for preparing a bimetallic functionalized organic framework material as claimed in claim 1, characterized in that: In the step S1, the reaction temperature is 110-150° C., the reaction time is 20-40 hours; the cooling temperature is 20-30° C.; the generated solid product is filtered and washed 2-4 times with DMF and methanol respectively; the drying condition is drying in a vacuum drying oven at 60-80° C. for 6-12 hours.

6. A method for preparing a bimetallic functionalized organic framework material as claimed in claim 1, characterized in that: In the step S2, the mass ratio of silver nitrate to UiO-66-SO3H is 51-272:107-214; the acetonitrile is a mixed solution of acetonitrile and water, wherein the volume ratio of acetonitrile to water is 1:0.8-1:1.

2.

7. A method for preparing a bimetallic functionalized organic framework material as claimed in claim 1, characterized in that: The reaction temperature in step S2 is 28-30° C., and the reaction time in the dark is 8-15 hours.

8. A method for preparing a bimetallic functionalized organic framework material as claimed in claim 1, characterized in that: In the step S2, the mixture is rinsed with water for 3-5 times; and the drying condition is 80-120° C. for 12-24 hours.

9. A bimetallic functionalized organic framework material, characterized in that: The compound is prepared by any one of the preparation methods of claims 1 to 8.

10. The method for applying a bimetallic functionalized organic framework material as claimed in claim 9, characterized in that: The application of the bimetallic functionalized organic framework material in carbon dioxide adsorption and separation.

Citation Information

Cited By

  • Preparation and application of amino-functionalized M-coated UiO-66-NH-2 composite adsorbent

    CN120022872A